PENGARUH PRESOR, MACHIAVELLIAN, PREFERENSI RISIKO, DAN KEKINIAN INFORMASI TERHADAP PENGAMBILAN KEPUTUSAN ETIS KONSULTAN PAJAK - Olivia Nadia Lisa Febriyani, 13.05.52.0205; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
This study examines the influence of presor, machiavellian, risk preference, the current information on the ethical decision making of tax consultants. This research was conducted at Tax Consultant Office of Semarang. The research used sample of tax consultant in Semarang City. The sampling method uses convenience sampling and determination of a minimum sample using the slovin formula. The analysis technique used is multiple linear regression with SPSS program. As a requirement for the test statistics have been tested normality and the classical assumption that the results show the data is normally distributed and pass from the classical assumption test. The results of this study indicate that the variable presor and the current information has no significant effect on ethical decision making tax consultant. While variable machiavellian and risk preference have a significant positive effect to ethical decision of tax consultant.Keywords: Presor, Machiavellian, Ris